Psychological evaluation of a virtual connected room from the perspective of we-mode - Harada, Yuki; Sato, Yoshihiro; Kambara, Ayumi; Oki, Kazuo; Takahashi, Ryo; Utsumi, Nobuyuki; Tsuji, Ryuhei; Sato, Yoshimichi (Frontiers in Virtual Reality, 2025)
A potential factor for video-meetings that negatively influences users’ psychological aspects is the reduction of the we-mode. The we-mode refers to a cognitive state in which team members share mental states, allowing them to coordinate actions based on each other’s conditions and enhance joint performance. To address this reduction, we developed a prototype video-meeting system (virtual connected room) designed to enhance the presence of users as if they were in the same room. This study evaluated the effectiveness of a virtual connected room from the perspective of the we-mode. In the experiment, a pair of participants performed three tasks in face-to-face, virtual connected, and display-based remote conditions. We used the referential communication task to evaluate the efficiency of communications and the joint Simon and number judgement tasks to evaluate the we-mode. The results showed that the virtual connected condition influenced the responses of joint Simon and number judgment, but did not influence the performance of the referential communication task. These results suggest that the virtual connected room promotes the we-mode.